Supersymmetric large tan(beta) corrections to DeltaM_(d,s) and B_(d,s) -> mu+mu- revisited - Freitas, A; Gasser, E; Haisch, U (2007)
We point out that in the minimal supersymmetric standard model terms from the mixing of Higgs and Goldstone bosons which are connected to the renormalization of tan(beta) via Slavnov-Taylor identities give rise to corrections that do not vanish in the limit where the supersymmetric particles are much heavier than the Higgs bosons. These additional contributions have important phenomenological implications as they can lead to potentially large supersymmetric effects in DeltaM_d and to a significant increase of DeltaM_s relative to the standard model prediction for a light pseudoscalar Higgs A0. We calculate all the missing one-loop pieces and combine them with the known effective non-holomorphic terms to obtain improved predictions for the B_(d,s)-anti-B_(d,s) mass differences DeltaM_(d,s) and the branching ratios of B_(d,s) -> mu+mu- in the large tan(beta) regime of the minimal supersymmetric standard model with minimal flavor violation.